Environmental Policy of the Lula government: The case of Amazonía - Souza, Helena (2010)
Does Brazil have “green” policy towards its Amazonian region? The author claims that Lula’s fierce rhetoric on environmental issues does not reflect the actual policies implemented by his government in the Brazilian Amazonian region. These policies, contrary to the government’s discourse, are favorable to the domestic and international exploitation of the natural resources found in the Amazonia.